Intramyocellular lipid content and lipogenic gene expression responses following a single bout of resistance type exercise differ between young and older men - Tsintzas, Kostas; Stephens, Francis B.; Snijders, Tim; Wall, Benjamin T.; Cooper, Scott; Mallinson, Joanne; Verdijk, Lex B.; van Loon, Luc J.C. (Elsevier, 2017)
The aim of this study was to examine the temporal relationship between intramyocellular lipid (IMCL) content and the expression of genes associated with IMCL turnover, fat metabolism, and inflammation during recovery from an acute bout of resistance type exercise in old versus young men. Seven healthy young (23 ± 2 years, 77.2±2.9 kg) and seven healthy older (72±1 years, 79.3±4.9 kg) males performed a single bout of resistance exercise involving 6 sets of 10 repetitions of leg press and 6 sets of 10 repetitions of leg extension at 75% one-repetition maximum (1-RM).Muscle biopsy samples were obtained before and 12, 24 and 48 h after the completion of exercise and analysed for IMCL content and the expression of 48 genes. The subjects refrained from further heavy physical exercise and consumed a standardized diet for the entire experimental period. The IMCL content was ~2-fold higher at baseline and 12 h post-exercise in old compared with young individuals. However, no differences between groups were apparent after 48 h of recovery. There was higher expression of genes involved in fatty acid synthesis (FASN and PPARγ) during the first 24 h of recovery. Differential responses to exercise were observed between groups for a number of genes indicating increased inflammatory response (IL6, IkBalpha, CREB1) and impaired fat metabolism and TCA cycle (LPL, ACAT1, SUCLG1) in older compared with younger individuals. A singe bout of resistance type exercise leads to molecular changes in skeletal muscle favouring reduced lipid oxidation, increased lipogenesis, and exaggerated inflammation during post-exercise recovery in the older compared with younger individuals, which may be indicative of a blunted response of IMCL turnover with ageing.